Electrophoretic Pattern of Hereditary Haemoglobin Disorders in Bangladesh - Uddin, Md. Kazim; Aziz, Md. A; Bhuya, Md. Fakhruddin; Dipta, Tashmim Farhana; Begum, Masuda; Yunus, ABM; Rahman, Md. Jalilur (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 58-60 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12546